Bully/victims: a longitudinal, population-based cohort study of their mental health. - Lereya, Suzet; Copeland, William; Zammit, Stanley; Wolke, Dieter (European Child & Adolescent Psychiatry, 2015)
It has been suggested that those who both bully and are victims of bullying (bully/victims) are at the highest risk of adverse mental health outcomes. However, unknown is whether most bully/victims were bullies or victims first and whether being a bully/victim is more detrimental to mental health than being a victim. A total of 4101 children were prospectively studied from birth, and structured interviews and questionnaires were used to assess bullying involvement at 10 years (elementary school) and 13 years of age (secondary school). Mental health (anxiety, depression, psychotic experiences) was assessed at 18 years. Most bully/victims at age 13 ( n = 233) had already been victims at primary school (pure victims: n = 97, 41.6 % or bully/victims: n = 47, 20.2 %). Very few of the bully/victims at 13 years had been pure bullies previously ( n = 7, 3 %). After adjusting for a wide range of confounders, both bully/victims and pure victims, whether stable or not from primary to secondary school, were at increased risk of mental health problems at 18 years of age. In conclusion, children who are bully/victims at secondary school were most likely to have been already bully/victims or victims at primary school. Children who are involved in bullying behaviour as either bully/victims or victims at either primary or secondary school are at increased risk of mental health problems in late adolescence regardless of the stability of victimization. Clinicians should consider any victimization as a risk factor for mental health problems.